2012
DOI: 10.1001/archsurg.2012.1094
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome in Relation to Timing of Surgery in Chronic Pancreatitis

Abstract: To evaluate the effect of timing of surgery on the long-term clinical outcome of surgery in chronic pancreatitis (CP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 38 publications
3
81
0
3
Order By: Relevance
“…Negi et al [87] conclude that patients should be referred for surgery before opiates are needed to relieve pain. These results are confirmed by Ahmed Ali et al [141], who found that duration of pain (>3 year), the number of endoscopic interventions (>5), and preoperative daily opioid use are independently associated with persistent severe pain after pancreatic surgery. Interestingly, this also applies for endoscopic treatment.…”
Section: Future Challenges: Timing Of Surgerysupporting
confidence: 72%
See 1 more Smart Citation
“…Negi et al [87] conclude that patients should be referred for surgery before opiates are needed to relieve pain. These results are confirmed by Ahmed Ali et al [141], who found that duration of pain (>3 year), the number of endoscopic interventions (>5), and preoperative daily opioid use are independently associated with persistent severe pain after pancreatic surgery. Interestingly, this also applies for endoscopic treatment.…”
Section: Future Challenges: Timing Of Surgerysupporting
confidence: 72%
“…Furthermore, tolerance, dependency, and adverse events are frequently reported drawbacks of opioid use and have a large impact on the quality of life and social functioning [140]. Likewise, several recent studies have shown that preoperative opioid use predisposes to failure of achieving complete long-term relief of pain after endoscopic and surgical intervention [21,46,87,141,142,143]. Negi et al [87] conclude that patients should be referred for surgery before opiates are needed to relieve pain.…”
Section: Future Challenges: Timing Of Surgerymentioning
confidence: 99%
“…A series on surgical treatment in chronic pancreatitis shows excellent long-term results [30]. The optimal timing of surgery, however, continues to be a point of debate [3, 4]. Whereas previously surgeons tried to hold off surgery until all medical and endoscopic options were exhausted, more recently others advocate early surgery because of its suggested superiority in treating pain.…”
Section: Step-up Approach For the Treatment Of Chronic Pancreatitis Painmentioning
confidence: 99%
“…Recently, multiple studies have suggested that early surgery is superior in providing pain relief and improvement of quality of life, compared to the step-up approach in which medical therapy is followed by endoscopy and finally surgery [4-6]. Delaying invasive treatment such as surgery was negatively associated in an observational study, with the duration of pre-operative opioid use, multiple endoscopic interventions and the duration of chronic pancreatitis [4].…”
Section: Timing Of Surgery In Chronic Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation